THU0515 C5orf30 A Novel Regulator of Tissue Damage in Rheumatoid Arthritis. (10th June 2014) - Muthana, M.; Davies, H.; Khetan, S.; Wright, F.; Hawtree, S.; Ciani, B.; Wilson, A.
Abstract : Background: A recent genome wide association study identified the variant rs26232 in the first intron of the uncharacterized gene, C5orf30, as a rheumatoid arthritis (RA) susceptibility variant 1 . In addition, it has been associated with severity of radiological joint damage suggesting a role in tissue breakdown 2 . To date there is no function assigned for C5orf30 and neither the gene or protein show homology to any known functional sequences. However, C5orf30 i s highly conserved in chimpanzee, dog, cow, mouse, chicken, and zebrafish (orthologs). Objectives: The aim of this study is to determine the biological roles of C5orf30 in rheumatoid arthritis. Methods: Immunohistochemistry on synovial samples was used to determine expression of C5orf30 including co-localisation using antibodies to macrophages (CD68), fibroblasts (5B5), T (CD3) & B (CD19) cells. Real time PCR and western blotting were used to examine C5orf30 transcript and protein levels in fibroblast-like synovial cells (FLS treated with TNF & hypoxia). To investigate gene function siRNA was used to knockdown (KD) either C5orf30 or a non-targeting control (NTC) in synovial FLS in vitro . After knockdown cell viability, proliferation, invasion and migration were all assessed and an Illumina BeadChip was used to analyse effects of siRNA-mediated C5orf30 repression on global gene expression. Results: Confocal microscopy revealed C5orf30 to be strongly expressed in both the cytoplasmic compartment of RA synovial lining cells including macrophages and fibroblasts, but not T & B cells. C5orf30 was undetectable in arthroscopy sections obtained from osteoarthritis or control synovium. C5orf30 was expressed in FLS and was found to be up-regulated by hypoxia (8-fold) and down-regulated by TNF treatment (0.5-fold). We found that C5orf30 KD did not affect cell viability and proliferation but increased the invasiveness of FLS assayed using Matrigel ( p =0.01) and increased FLS migration in a scratch wound assay ( p =0.02) (n=6). In support of this gene profiling studies revealed upregulation of cell migration, adhesion, angiogenesis, and immune and inflammatory pathways as a result of C5orf30KD . Conclusions: C5orf30 is expressed in synovial cells and to a much lesser extent in circulating peripheral blood leukocytes obtained from RA patients. C5orf30 knockdown increased FLS migration and invasion into matrigel confirming that C5orf30 is a negative regulator of tissue breakdown. References: Stahl EA, Raychaudhuri S, Remmers EF, et al. Genome-wide association study meta-analysis identifies seven new rheumatoid arthritis risk loci. Nat Genet 2010;42:508-14. Teare MD, Knevel R, Morgan MD, et al. Allele-Dose Association of the C5orf30 rs26232 Variant With Joint Damage in Rheumatoid Arthritis. Arthritis Rheum. 2013;65:2555-61. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4284